Academic Administration of Schools Expanding Educational Opportunities under the Trat Primary Educational Service Area Office - จิตมณีธรรม, พีระพัฒน์; ประวัติรุ่งเรือง, ปราศรัย; แก้วมงคล, ทรงยศ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: 1) study the academic administration of the schools expanding educational opportunities 2) compare the academic administration of the schools expanding educational opportunities classified according to gender, work experience and school size. 3) study  guidelines for academic administration in schools expanding educational opportunities under the Trat Primary Educational Service Area Office. The research sample consisted of 214 school administrators and teachers from schools under the Trat Primary Educational Service Area Office in the 2025 academic year. The sample size was determined using the Krejcie and Morgan table (1970). The sampling process involved stratified random sampling followed by simple random sampling. The research instrument was a questionnaire with a reliability coefficient of .975. Data were analyzed using frequency, percentage, mean, standard deviation, t-test and f-test, One-Way ANOVA; the qualitative phase collected data through interviews with three experts selected through purposive sampling, the instrument used for data collection was a semi-structured interview, and the data were analyzed using content analysis.           The research findings revealed that: 1) The overall academic administration of schools expanding educational opportunities under the Trat Primary Educational Service Area Office was at a high level. Considering each individual aspect, learning process development was at the highest level. The remaining four aspects were at a high level, including: school curriculum development; measurement, evaluation, and credit transfer; educational supervision; and development of internal quality assurance systems and educational standards. 2) The comparison of academic administration in educational opportunity expansion schools under the Trat Primary Educational Service Area Office, classified by gender showed significant difference based on gender at the .01 level, work experience, and school size, found that there were no significant differences. 3) Guidelines for Academic Administration in Educational Opportunity Expansion Schools under the Trat Primary Educational Service Area Office. The findings revealed that there were five aspects with fifteen guidelines, including school curriculum development, learning process development, measurement and evaluation, educational supervision, and the development of the internal quality assurance system. Each aspect focuses on enhancing students’ quality and improving the effectiveness of educational management in schools, in accordance with the school context and learners’ needs.